Flow-Representation Approach For ICMPV6-Based Ddos Attacks Detection - Elejla, Omar E. O. (2018)
In addition to the address expandability, IPv6 broughts new functionalities, such as Neighbor Discovery Protocol (NDP) and address auto-configuration scheme, which depends on Internet Control Message Protocol version 6 (ICMPv6) protocol. ICMPv6 is delegated with more responsibilities than Internet Control Message Protocol version 4 (ICMPv4) in IPv4, and it is considered the backbone and the mandatory part in IPv6 native networks. IPv6 is vulnerable to a number of attacks from IPv4, besides new attacks have appeared within its new features. The most popular IPv6 attacks are Denial of Service (DoS) and its distributed version (DDoS) that use ICMPv6 messages. ICMPv6-based DoS & DDoS attacks are one of the major problems of today’s Internet, impacting economic damages in some serious cases.